2021
DOI: 10.3390/proteomes9030038
|View full text |Cite
|
Sign up to set email alerts
|

Proteomes Are of Proteoforms: Embracing the Complexity

Abstract: Proteomes are complex—much more so than genomes or transcriptomes. Thus, simplifying their analysis does not simplify the issue. Proteomes are of proteoforms, not canonical proteins. While having a catalogue of amino acid sequences provides invaluable information, this is the Proteome-lite. To dissect biological mechanisms and identify critical biomarkers/drug targets, we must assess the myriad of proteoforms that arise at any point before, after, and between translation and transcription (e.g., isoforms, spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 273 publications
(550 reference statements)
1
71
0
1
Order By: Relevance
“…Another recent study identified age‐related changes in the proteomic profiles of OPC from Sprague Dawley rats; notably, proteins associated with inflammatory responses were found to increase with aging (de la Fuente et al, 2020). However, none of these studies sought to analyze proteoforms (i.e., the active biological entities; Bogaert et al, 2020; Carbonara et al, 2021; Coorssen & Yergey, 2015; Sen et al, 2021; Zhan et al, 2019). Thus, an appropriately designed (top‐down) proteomic analysis may identify age‐dependent changes in specific proteoforms related to microglial (and astrocytic) function.…”
Section: The Effect Of Aging On Microglia and Astrocytes And Myelinationmentioning
confidence: 99%
“…Another recent study identified age‐related changes in the proteomic profiles of OPC from Sprague Dawley rats; notably, proteins associated with inflammatory responses were found to increase with aging (de la Fuente et al, 2020). However, none of these studies sought to analyze proteoforms (i.e., the active biological entities; Bogaert et al, 2020; Carbonara et al, 2021; Coorssen & Yergey, 2015; Sen et al, 2021; Zhan et al, 2019). Thus, an appropriately designed (top‐down) proteomic analysis may identify age‐dependent changes in specific proteoforms related to microglial (and astrocytic) function.…”
Section: The Effect Of Aging On Microglia and Astrocytes And Myelinationmentioning
confidence: 99%
“…In this study, alterations were observed in the abundance of actin proteoforms and other actinassociated proteins. Proteoforms are variations in proteins arising from a single gene via multiple mechanisms, such as alternative splicing and post-translation modifications [41]. The proteoforms vary in their expression patterns in physiological states, and thus, have been used as biomarkers of health and diseases [42].…”
Section: Discussionmentioning
confidence: 99%
“…An important consideration for this study is that identifications are based on peptides derived from canonical sequences of public databases, and subsequent validation studies will need to take into account the complexity of associated proteoforms that may be present (for example, splice variants and post-translational modifications (PTMs)), when designing these studies [ 96 ].…”
Section: Discussionmentioning
confidence: 99%